Analgesic potential of PF-06372865, an α2/α3/α5 subtype-selective GABA(A) partial agonist, in humans - van Amerongen, Guido (Br J Anaesth, 2019)
BACKGROUND: This study investigated the analgesic effects of two doses (15 and 65 mg) of PF-06372865, a novel α2/α3/α5 gamma-aminobutyric acid A (GABA(A)) subunit selective partial positive allosteric modulator (PAM), compared with placebo and pregabalin (300 mg) as a positive control. METHODS: We performed a randomised placebo-controlled crossover study (NCT02238717) in 20 healthy subjects, using a battery of pain tasks (electrical, pressure, heat, cold and inflammatory pain, including a paradigm of conditioned pain modulation). Pharmacodynamic measurements were performed at baseline and up to 10 h after dose. RESULTS: A dose of 15 mg PF-06372865 increased pain tolerance thresholds (PTTs) for pressure pain at a ratio of 1.11 (90% confidence interval [CI]: 1.02, 1.22) compared with placebo. A dose of 65 mg PF-06372865 led to an increase in PTT for the cold pressor at a ratio of 1.17 (90% CI: 1.03, 1.32), and pressure pain task: 1.11 (90% CI: 1.01, 1.21). Pregabalin showed an increase in PTT for pressure pain at a ratio of 1.15 (95% CI: 1.06, 1.26) and cold pressor task: 1.31 (90% CI: 1.16, 1.48). CONCLUSION: We conclude that PF-06372865 has analgesic potential at doses that do not induce significant sedation or other intolerable adverse events limiting its clinical use. In addition, the present study established the potential role for this battery of pain tasks as a tool in the development of analgesics with a novel mechanism of action, for the treatment of various pain states including neuropathic pain and to establish proof-of-concept. CLINICAL TRIALS REGISTRATION: NCT0223871.